2012
DOI: 10.1128/mcb.00182-12
|View full text |Cite
|
Sign up to set email alerts
|

The Super Elongation Complex Family of RNA Polymerase II Elongation Factors: Gene Target Specificity and Transcriptional Output

Abstract: The elongation stage of transcription is highly regulated in metazoans. We previously purified the AFF1-and AFF4-containing super elongation complex (SEC) as a major regulator of development and cancer pathogenesis. Here, we report the biochemical isolation of SEC-like 2 (SEC-L2) and SEC-like 3 (SEC-L3) containing AFF2 and AFF3 in association with P-TEFb, ENL/MLLT1, and AF9/MLLT3. The SEC family members demonstrate high levels of polymerase II (Pol II) C-terminal domain kinase activity; however, only SEC is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
217
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(227 citation statements)
references
References 61 publications
(99 reference statements)
6
217
0
4
Order By: Relevance
“…S1), a positive regulator of P-TEFb (33,34). Because the AF9 and ENL C-terminal domains interact competitively with AFF4 (23,29,30), we analyzed one of the paralogs, ENL. To purify complexes of HIV-1 Tat and P-TEFb, we adapted baculovirus coexpression strategies (35).…”
Section: Aff4 Directly Assembles Components Through Distinct Binding mentioning
confidence: 99%
See 3 more Smart Citations
“…S1), a positive regulator of P-TEFb (33,34). Because the AF9 and ENL C-terminal domains interact competitively with AFF4 (23,29,30), we analyzed one of the paralogs, ENL. To purify complexes of HIV-1 Tat and P-TEFb, we adapted baculovirus coexpression strategies (35).…”
Section: Aff4 Directly Assembles Components Through Distinct Binding mentioning
confidence: 99%
“…In vivo, AFF4 recruits SEC components through defined regions in the first 900 amino acids (23,29,30). AFF4 associates in vivo with P-TEFb, AFF4 300-600 recruits the C-terminus of ELL2, and AFF4 600-900 binds competitively to the C-terminal domain of homologs ENL and AF9.…”
Section: Aff4 Directly Assembles Components Through Distinct Binding mentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, it has been shown that SEC is required for c-Myc expression in several leukemia cell lines, suggesting that SEC is a potential therapeutic target for the treatment of leukemia and other solid cancers associated with overexpression of the c-Myc gene [35]. p53 has also been shown to repress the expression of c-Myc [36]; however, the mechanism by which p53 regulates the expression of c-Myc has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%